Transcriptomic Profiling of Apple Calli With a Focus on the Key Genes for ALA-Induced Anthocyanin Accumulation - Zheng, Jie; Liu, Longbo; Tao, Huihui; An, Yuyan; Wang, Liangju (Frontiers in Plant Science, 2021)
The red color is an attractive trait of fruit and determines its market acceptance. 5-Aminolevulinic acid (ALA), an eco-friendly plant growth regulator, has played a universal role in plant secondary metabolism regulation, particularly in flavonoids biosynthesis. It has been widely reported that ALA can up-regulate expression levels of several structural genes related to flavonoids metabolism and anthocyanin accumulation. However, the molecular mechanisms behind ALA-induced expression of these genes are complicated and still far from being completely understood. In this study, transcriptome analysis identified the differentially expressed genes (DEGs) associated with ALA-induced anthocyanin accumulation. KEGG (Kyoto Encyclopedia of Genes and Genomes) analysis showed that the flavonoid biosynthesis (ko00941) pathway was significantly enhanced in the ALA-treated apple calli at 24, 48 and 72 h after the treatment. Expression pattern revealed that ALA upregulated the expression of the structural genes not only related to anthocyanin biosynthesis (MdCHS, MdCHI, MdF3′H, MdDFR, MdANS, and MdUFGT), but also anthocyanin transport (MdGST and MdMATE). Two R2R3-MYB transcription factors (MdMYB10 and MdMYB9), which are the known positive regulators of anthocyanin biosynthesis, were significantly induced by ALA. Gene overexpression and RNA interference assays demonstrated that MdMYB10 and MdMYB9 were involved in ALA-induced anthocyanin biosynthesis. Moreover, MdMYB10 and MdMYB9 might positively regulate the transcription of MdMATE8 by binding to the promoter region. These results indicate that MdMYB10 and MdMYB9 modulated structural genes expression of anthocyanin biosynthesis and transport in response to ALA-mediated apple calli coloration at the transcript level. We herein provide new details regarding transcriptional regulation of ALA-induced color development.